Encapsulated Object Analysis: Imaging and Analysis of Encapsulated Objects through Self‐Assembled Electron and Optically Transparent Graphene Oxide Membranes (Adv. Mater. Interfaces 2/2017). Issue 2 (January 2017) - Yulaev, Alexander; Lipatov, Alexey; Lu, Annie Xi; Sinitskii, Alexander; Leite, Marina S.; Kolmakov, Andrei
Abstract : Andrei Kolmakov and co‐workers demonstrate a facile dropcasting technique for encapsulation and adhesion of micro‐ and nanoobjects on arbitrary substrates, stencils, and microstructured surfaces by ultrathin graphene oxide membranes in article 1600734. Such membranes are mechanically robust, chemically protective, and yet highly transparent to electrons and photons. Thus, the membranes enable electron/optical microscopy and spectroscopy to be performed on encapsulated objects.